Pengaruh Good Corporate Governance dan Green Accounting terhadap Nilai Perusahaan - Tiara Aisyah Putri; Siti Khairani (Universitas Multi Data Palembang, 2026)
This study aims to examine the effect of Good Corporate Governance (GCG) disclosure through the managerial ownership mechanism and Green Accounting on firm value in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The sample was selected using a purposive sampling technique, resulting in 28 companies. Data analysis was conducted using multiple linear regression analysis. The results indicate that GCG disclosure through the managerial ownership mechanism has no significant effect on firm value, while Green Accounting has a significant effect on firm value.